A Clinical Study on Vitamin D deficiency in Hypothyroidism - PRIYA, NEHA; KUMARI, RINA; P WAGH, SURAJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Vitamin D deficiency is a concern of global health nowadays. Although its main role is in regulating bone metabolism, over the past few decades, its impact on non-skeletal actions has been studied. Its role as an immune modulator has been recently emphasized. Recent evidence is increasingly pointed toward the significant role of vitamin D in reducing the incidence of autoimmune diseases. Aims & Objectives: In the present study, we aimed to determine the relationship between hypothyroidism and Vitamin D deficiency. Methods: It was an Observational Study, a study conducted in the Department of Biochemistry at MGM Medical College & LSK Hospital Kishanganj, Bihar. In the present study, 50 patients and 50 healthy age and sex-matched controls were included during the study period from June 2021 to March 2022. Serum vitamin D (25-OH) levels were measured in all the patients. Vitamin D deficiency was designated at levels lower than 20 ng/ml. Thyroid hormones (TSH, T3, and T4) were also evaluated in all participants. Results: Incidence of vitamin D deficiency is significantly high among hypothyroid patients compared to normal controls (p-value = 0.036). The mean level of Vitamin D was significantly low level among patients with hypothyroidism compared to controls (23.57 ±9.77 vs. 31.20 ±10.23 ng/ml, p-value =0.02). Pearson's correlation between vitamin D level and thyroid profile among hypothyroid cases revealed that there was a significant negative correlation between serum Vitamin D and TSH level (p-value = <0.0001). Conclusion: Deficiency of vitamin D is significantly associated with hypothyroidism, and therefore screening of vitamin D is essential for all hypothyroid patients.